APPLICATIONS OF HOLLAND'S VOCATIONAL THEORY TO COUNSELLING PRACTICE RELATED TO VOCATIONAL EDUCATION - Caron, Andrew D. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1994)
Holland's (1985) theory of vocational choice and adjustment has proved immensely influential in career counselling practice, the development of interest inventories, and the organization of occupational information used in a wide range of applied settings. lt is not, however, immune to misapplication in the counselling and assessment process by counsellors who may permit any of a number of systematic distortions to affect the process of matching clients to suitable vocational directions. Several likely sources of such distortion are reviewed in the context of counselling English-language students as to the advisability of entering vocational education programs in the province of Quebec. Recommendations are made for the development of cost-efficient career intervention systems and improvements in career counsellor training programs. RÉSUMÉ La théorie de Holland (1985) sur le choix et l'adaptation professionnels s'est révélée immensément influente dans le domaine de l'orientation professionnelle, la conception de répertoires d'intérêts et la structuration de renseignements professionnels utilisés dans un vaste éventail de cadres pratiques. Elle n'est toutefois pas à l'abri d'un usage impropre par les conseillers d'orientation et d'évaluation qui peuvent dénaturer comme ils l'entendent le processus qui consiste à trouver l'orientation professionnelle qui convient à leurs clients. Plusieurs sources potentielles de pareilles distorsions sont analysées dans le contexte de l'orientation d'étudiants anglophones sous l'angle de l'intérêt qu'il y a à s'inscrire à des programmes de la formation professionnelle dans la province de Québec. Des recommandations sont faites pour la conception de systèmes d'intervention professionnels rentables et l'amélioration des programmes de formation des conseillers professionnels.